Is There Something Unique About Marriage? The Relative Impact of Marital Status on Alcohol Consumption Among Military Personnel. Issue 1 (2nd January 2016) - Liew, Hui
ABSTRACT: This study seeks to empirically derive the patterns of alcohol consumption among military personnel by forming clusters of military personnel with similar alcohol use and sociodemographic characteristics. The empirical work of this study is based on the 2011 National Survey on Drug Use and Health. Findings suggest that alcohol consumption varies according to marital status, education level, and other demographic characteristics (age, sex, and race). Frequent heavy drinking is concentrated among military personnel who are unmarried, between the ages of 18 and 25, non-Hispanic Whites, and men. Tailoring and customizing delivery approaches to focus on the patterns of alcohol consumption as well as the socioeconomic characteristics of the different segments of military personnel in United States could also be a promising alternative.